MENINGKATKAN HASIL BELAJAR SISWA KELAS X PADA KONSEP KEANEKARAGAMAN HAYATI MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI - Almira Ulimaz (Universitas Islam Balitar, 2015)
This study is aimed at seeing how inquiry model improves students ’ mastery on the subject diversity of biological resources. This study implements classroom action desearch design with two cycles and assigned the grade X students of SMAN 10 Banjarmasin as the research subject. Data were collected from cognitive product of students ’ learning, scores of pretest and posttest. Data were analyzed using descriptive statistics. The findings of the study are as follows: in cycle I students ’ mastery is 75.75% and improvement was achieved in the cycle II achieving 93.94%. The achievement indicates students mastery on 85%.